Kajian Pemanfaatan Sistem Informasi Manajemen Rumah Sakit di Instalasi Farmasi dan Pengadaan Peralatan Medik di RSU GMIM Siloam Sonder - Saranita V. G. Polii; Gustaaf A. E. Ratag; Fatimawali Fatimawali (e-CliniC, 2023)
Abstract: Hospital management information system (HMIS) processes and integrates the entire flow of hospital service processes to obtain precise and accurate information. This study aimed to analyze the use of HMIS in the management of drugs and consumable medical materials at the Pharmacy Installation and procurement of medical equipment in RSU GMIM Siloam Sonder. This was a qualitative and descriptive study using purposive sampling technique. There were nine informants in this study. Data were obtained from in-depth interviews, document searches, direct surveys, and comparing with theories in the literatures. The results showed that managements of drugs and consumables medical materials at the Pharmacy Installation had used the HMIS which supported the development of service performance in the hospital, improved users’ skills, easy to be understood and learnt, and hospital employees received training in operating the HMIS, however, it was not optimal. Its operation was also supported by a computer that was easy to operate, however, some difficulties used to occur. Moreover, the process of procuring medical equipment did not involve the HMIS. In conclusion, the HMIS at RSU GMIM Siloam Sonder has been used in management of drugs and consumables medical materials at the Pharmacy Installation, albeit, it has not been used in the process of procuring medical equipment. Keywords: HMIS; drugs and consumable medical materials; procurement of medical equipment Abstrak: Sistem informasi manajemen rumah sakit (SIM RS) memroses dan mengintegrasikan seluruh alur proses pelayanan rumah sakit untuk memperoleh informasi secara tepat dan akurat. Penelitian ini bertujuan untuk menganalisis pemanfaatan SIM RS dalam pengelolaan obat dan bahan medis habis pakai (BHP) di Instalasi Farmasi dan pengadaan peralatan medik di RSU GMIM Siloam Sonder. Jenis penelitian ialah deskriptif kualitatif dengan menggunakan teknik purposive sampling. Informan penelitian ini berjumlah sembilan orang. Data diperoleh dari hasil wawancara mendalam, penelusuran dokumen, survei langsung, serta membandingkan dengan teori-teori pada literatur. Hasil penelitian menunjukkan bahwa kegiatan pengelolaan obat dan BHP di Instalasi Farmasi RSU GMIM Siloam Sonder sudah memanfaatkan SIM RS yang mendukung pengembangan kinerja pelayanan di rumah sakit, meningkatkan keterampilan penggunanya, mudah dipahami dan dipelajari, serta karyawan mendapatkan pelatihan dalam mengoperasikan SIM RS, namun belum maksimal. Pengoperasiannya didukung juga oleh komputer yang mudah dioperasikan, namun masih sering terdapat kesulitan. Proses pengadaan peralatan medik belum melibatkan SIM RS. Simpulan penelitian ini ialah SIM RS di RSU GMIM Siloam Sonder sudah dimanfaatkan dalam kegiatan pengelolaan obat dan BHP namun belum dimanfaatkan dalam proses pengadaan peralatan medik. Kata kunci: SIM RS; obat dan bahan habis pakai; pengadaan peralatan medik